Resposta :
Resposta:
Sn= 208
Explicação passo a passo:
an=a1+(n-1).r
34=-2+(n-1).3
34=5 .3n
n=39/3
an=13
Sn= (a1+an).n/2
Sn=(-2+34).13/2
Sn=416/2
Sn=208
[tex] > resolucao \\ \\ \geqslant progressao \: \: aritmetica \\ \\ r = a2 - a1 \\ r = 1 - ( - 2) \\ r = 1 + 2 \\ r = 3 \\ \\ an = a1 + (n - 1)r \\ 34 = - 2 + (n - 1)3 \\ 34 = - 2 + 3n - 3 \\ 34 = - 5 + 3n \\ 34 + 5 = 3n \\ 39 = 3n \\ n = \frac{39}{3} \\ n = 13 \\ \\ \\ \geqslant \: soma \: dos \: termos \: da \: pa \\ \\ sn = \frac{(a1 + an)n}{2} \\ \\ sn = \frac{( - 2 + 34)13}{2} \\ \\ sn = \frac{32 \times 13}{2} \\ \\ sn = 16 \times 13 \\ \\ sn = 208 \\ \\ \geqslant \leqslant \geqslant \leqslant \geqslant \leqslant \geqslant \geqslant \geqslant [/tex]
![Ver imagem EWERTON197775P7GWLB](https://pt-static.z-dn.net/files/df1/e50f694f808de138d5a0a87ee71c6249.jpg)